(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
Speech goes in the article about language realizations of sound images in the cinematic story of Alexander Dovzhenko «Enchanted Desna». It is determined that for the depicting of auditory images the author uses lexemes with direct nomination, metaphorical compounds, as well as names of objects and phenomena that thus cause associative sound impressions. The means of the recording in the cinematic story are volumetric lexemes.